Anemia and Celiac Disease-Experience At Tertiary Care Center of Northern India - Malhotra, Parveen; Malhotra, Naveen; Malhotra, Vani; Pansi; Chhabra, Sonia; Chugh, Ajay; Chaturvedi, Abhishek; Chandrika, Parul (Journal of Hematology Research, 2015)
Background: Celiac disease (CD), is a chronic immune-mediated disorder of small intestine that occurs in genetically predisposed populations. It is characterized by permanent intolerance to wheat gliadins and other cereal prolamins. The epidemiology of CD has iceberg characteristics with more undiagnosed cases. The diagnosis of CD is currently based on both typical small bowel biopsy findings with clinical and serological parameters. Anemia secondary to iron, folic acid and vitamin B12 malabsorption is a common complication of celiac disease. Patients can also present with thrombocytosis, thrombocytopenia, leukopenia, venous thromboembolism, hyposplenism and IgA deficiency. Aims: This study conducted with aims to study presenting complaints of suspected cases of celiac disease and further correlate endoscopic duodenal biopsies with various clinical and serological parameters. Materials and Methods: The detailed clinical history and physical examination was done and then duodenum biopsies in hundred cases of suspected CD (on the basis of clinical and serological profile) were taken. Histopathological diagnosis was established on routine hematoxylin and eosin stained sections. The histopathological grading was performed as per modified Marsh grading. Representative section was also subjected for immunohistochemically staining with antihuman CD3 antibody for evaluating intraepithelial lymphocytes. Comparison of these grades with the serological (anti tTG levels) and other clinical parameters (symptoms, weight, endoscopy and hemoglobin levels) were done. These data were subsequently analyzed using SPSS 20.0 software. Chi square test and other relevant statistics were used to assess the relationship between two variables. P-value less than 0.05 was accepted as statistically significant. Results and Conclusions: Majority of patients presented with typical gastrointestinal symptoms and anemia and significantly correlated with higher Marsh grades (p=0.0326) but atypical symptoms can be the primary presentation of the disease. Patients with higher serum anti-tTG levels, have a high-degree probability of duodenal damage. Anti-tTG levels have conclusively been proven to correlate with increasing histological grades (p=0.005).